2008
DOI: 10.1016/j.micpath.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of message for FcεRI α chain blocks mast cell IL-4 production induced by co-culture with Mycoplasma pneumoniae

Abstract: We have previously described the activation of RBL-2H3 mast cells for IL-4 production by Mycoplasma pneumoniae but the mechanism remains unclear. M. pneumoniae binds eukaryotic cells primarily through sialoglycoproteins on the target cell surface. This study was undertaken to determine whether the sialated FcεRIα chain on RBL cells is important for M. pneumoniae-induced IL-4 production. We found that IgE-mediated IL-4 release by a series of RBL sublines correlated with the release induced by M. pneumoniae. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Mast cell cytokine production is dependent upon the presence of sialic acid residues on the target cell membrane and the P1 adhesin. More recent studies have revealed that the activation process requires expression of the heavily sialylated FcɛRI α chain by the mast cell (Luo et al , 2007). A model of cellular activation has been developed in which adherence by the bacterium to surface sialoglycoproteins results in cellular activation through the normal receptor‐signaling mechanisms.…”
Section: Interaction With Host Immune Cells and Autoimmunitymentioning
confidence: 99%
“…Mast cell cytokine production is dependent upon the presence of sialic acid residues on the target cell membrane and the P1 adhesin. More recent studies have revealed that the activation process requires expression of the heavily sialylated FcɛRI α chain by the mast cell (Luo et al , 2007). A model of cellular activation has been developed in which adherence by the bacterium to surface sialoglycoproteins results in cellular activation through the normal receptor‐signaling mechanisms.…”
Section: Interaction With Host Immune Cells and Autoimmunitymentioning
confidence: 99%
“…Two recent studies by Hoek and colleagues demonstate how M. pneumoniae stimulates production of IL-4 by mast cells in co-culture experiments [25,26]. Cytokine production by mast cells is dependent upon the presence of sialic acid residues on the target cell membrane and the P1 adhesin components of the attachment organelle, and requires expression of the heavily sialylated FcεRI α-chain by the mast cell [26].…”
Section: Innate and Adaptive Immune Responsementioning
confidence: 99%
“…Cytokine production by mast cells is dependent upon the presence of sialic acid residues on the target cell membrane and the P1 adhesin components of the attachment organelle, and requires expression of the heavily sialylated FcεRI α-chain by the mast cell [26]. Mycoplasma adherence to surface sialoglycoproteins results in cellular activation through the normal receptor signaling mechanisms.…”
Section: Innate and Adaptive Immune Responsementioning
confidence: 99%